Isidore of Seville, his Mode of Writing and the Metaphor of Taste = Isidoro de Sevilla, su modo de escribir y la metáfora del gusto - Voroncov, Sergej Alekseevič (Isidorianum, 2024)
The writings in which an author expresses his thought may actually be the product of certain cultural practices of his age. The article considers how such practices are manifested in the writings of Isidore of Seville, particularly with respect to the meaning of the metaphor of taste. Isidore borrows this metaphor from texts that explain the process of understanding Scripture and applies it to the achievement of wisdom. On the one hand, the metaphor stresses the transformative aspect of understanding (rather than the informative, scientia). It focuses on the special experience of the reader who senses the sweetness of the text, and not on the application of the text to one's life. On the other hand, reading and writing were imagined in terms related to food. The text was food that had to be prepared, to "read" meant to "taste", to "meditate" on it meant to "ruminate". Against this background, the writings of Isidore seem to appeal to the memory of the reader and his ability to meditate upon the text and, finally, to experience the taste of wisdom. Only the outermost level of texts was intended to inform the reader.